Tree Diversity, Abundance And Dominance In The Lakeside Vegetation of Dhaka City, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2023)
The present article deals with evaluating tree diversity, abundance, and dominance in the urban lakeside vegetation of Dhaka city. Data were collected using systematic sampling methods along with the transect lines. Visitor’s perceptions about existing tree diversity were also collected. A total of 2322 individuals under 118 tree species in 39 families were recorded from Dhanmondi, Hatirjheel and Gulshan lakeside vegetations. The origin analysis of tree species revealed that 39% areexotic and 61% are native. Among the tree species, the five most abundant areSwieteniamahagoni, Mangiferaindica, Cocos nucifera, Khayaanthothecaand Delonixregia. In these abundant tree species, three are exotic,such as Swieteniamahagoni, Khayaanthotheca, and Delonixregia, and the rest are native. According to the importance value index, the most five dominant tree species are Swieteniamahagoni, Samaneasaman, Cocos nucifera, Mangiferaindica, and Delonixregia. Likewise, among the top five dominant tree species, three are exotic, such as Swieteniamahagoni, Sananeasaman, andDelonixregia; the rest are native. The maximum number of tree species in the study areas are ornamental (25%), followed by medicinal (23%), fruit-bearing (22%), timber-producing (19%), and wildlife-supporting (11%). The maximum value of the Shannon diversity index was found in Dhanmondi (3.78), followed by Gulshan (3.41), and Hatirjheel (3.34). According to visitors’ perceptions, 85% of visitors favored positive actions regarding different management issues forlakeside tree diversity to enhance ecosystem services. A number of threats were identified for tree diversity in the study areas and suggested a number of recommendations for the management of tree diversity in three lakesides of vegetation (Dhanmondi, Hatirjheel, and Gulshan) to improve ecosystem services in the future.Bangladesh J. Plant Taxon. 30(2): 263-275, 2023 (December)